Governance and Funding of Voluntary Secondary Schools in Ireland - Smyth, Emer; Darmody, Merike (ESRI, 2013)
This study presents a comprehensive picture of educational governance and financing across the three different sectors of second-level schools in Ireland, namely, voluntary secondary schools, vocational schools, and community/comprehensive schools.
PUBLISHED
Dublin
Keywords: Schools; Funding